A Critique on the Book In Search of Persian Pottery - Leila Ghaffari; Davoud Ranjbaran (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Mitsukuni Yoshida, a former professor and director of Kyoto University, is one of the Japanese researchers in the field of Persian Pottery studies who has traveled to various historical and archeological sites in Iran and also Hormoz Island in the 1960s. He has written his findings on the history and techniques of creating Persian Pottery in the form of a book entitled In Search of Persian Pottery. In this article, by reviewing the present book as a worthwhile source in the field of Persian Pottery History, the author's perception of the evolution of this ancient art and the type of his encounter with the category of stylistics Persian Pottery has been reviewed. On this basis, Yoshida's view was not only to describe his observations of Persian Pottery, but also to study the stylistics and works of Persian Pottery in terms of recognizing their cultural and linguistic origins. Considering his membership in the Japan Anthropological Institute, his treatment of the anthropological aspects of the art of Pottery in this work is not far off. Also, the role of cultural commonalities of the Oriental countries in shaping his attitude towards Pottery and Persian Pottery as an Oriental researcher is important.